Hybrid infrastructures: The role of strategy and compromise in grassroot governance - Benedikt Schmid (Environmental Policy and Governance, 2021)
Contemporary trajectories of unsustainability and injustice require a profound restructuring of political, economic, and cultural institutions not sufficiently reflected in top-down governance. Diverse bottom-up actors and organizations that attempt to practice and institute more sustainable and just relations, in turn, have to tackle unfavorable conditions and generally lack the resources to take full effect. This paper critically discusses the role of strategy and compromise in facing this cycle of institutional inertia and lack of bottom-up agency. To illustrate its argument, the paper draws on an ethnographic case study on community-led initiatives in Stuttgart (Germany). It traces the ways in which a particular arrangement—an “open workshop”—supports individuals and organizations in their engagement in sustainability-oriented activities while substantiating ethically and socially ambiguous practices. Building on these empirical insights, the paper develops a notion of strategy that revolves around the reflective construction of hybrid but transformative infrastructures to strike a balance between ethical congruency and transformative pragmatism.
Keywords: 330; degrowth; postcapitalism; hybridity; infrastructure; strategy; transformation; activist scholarship